1996
DOI: 10.1523/jneurosci.16-17-05344.1996
|View full text |Cite
|
Sign up to set email alerts
|

A Distinct Pattern of Trophic Factor Expression in Myelin-Deficient Nerves ofTremblerMice: Implications for Trophic Support by Schwann Cells

Abstract: Distal to a peripheral nerve transection, myelin degradation and Schwann cell (SC) proliferation are accompanied by a marked upregulation of brain-derived neurotrophic factor (BDNF) and a decrease of ciliary neurotrophic factor (CNTF) in non-neuronal cells. To investigate the role of SC differentiation in trophic factor regulation, we studied BDNF and CNTF expression in sciatic nerves from Trembler-J (Tr-J) mice. In these animals, a mutation in the pmp-22 gene causes a failure of myelination and continuous SC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
3

Year Published

1998
1998
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 40 publications
(51 reference statements)
3
29
0
3
Order By: Relevance
“…Demyelination, remyelination, inflammatory cell infiltration, and onion bulb formation have been found in spinal nerve roots in acute 18 and chronic 15,30,31,35 inflammatory demyelinating polyradiculoneuropathies. Demyelinative changes in both peripheral nerves and spinal nerve roots have also been reported in hypertrophic hereditary motor and sensory neuropathy, 4 protein zero-deficient mice, 9,26 peripheral myelin protein-22 deficient mice, 40 Trembler mice, 2 and Trembler-J mice 13 and in animal models of inflammatory demyelinating neuropathy. 1,14,17,24,38,39 In 2 mice with POEMS, which is a monoclonal plasma cell disorder characterized by polyneuropathy (P), organomegaly (O), endocrinopathy (E), monoclonal gammopathy (M), and skin changes (S), spinal nerve roots and sural nerves showed the same pathologic changes of demyelination, remyelination, and inflammatory cell infiltration, 42,47 and in 3 cases of diabetic neuropathy, there was severe loss of both large and small MF in sural nerves while segmental demyelination and remyelination was the main finding in both dorsal and ventral spinal roots.…”
Section: Discussionmentioning
confidence: 90%
“…Demyelination, remyelination, inflammatory cell infiltration, and onion bulb formation have been found in spinal nerve roots in acute 18 and chronic 15,30,31,35 inflammatory demyelinating polyradiculoneuropathies. Demyelinative changes in both peripheral nerves and spinal nerve roots have also been reported in hypertrophic hereditary motor and sensory neuropathy, 4 protein zero-deficient mice, 9,26 peripheral myelin protein-22 deficient mice, 40 Trembler mice, 2 and Trembler-J mice 13 and in animal models of inflammatory demyelinating neuropathy. 1,14,17,24,38,39 In 2 mice with POEMS, which is a monoclonal plasma cell disorder characterized by polyneuropathy (P), organomegaly (O), endocrinopathy (E), monoclonal gammopathy (M), and skin changes (S), spinal nerve roots and sural nerves showed the same pathologic changes of demyelination, remyelination, and inflammatory cell infiltration, 42,47 and in 3 cases of diabetic neuropathy, there was severe loss of both large and small MF in sural nerves while segmental demyelination and remyelination was the main finding in both dorsal and ventral spinal roots.…”
Section: Discussionmentioning
confidence: 90%
“…Interestingly, it has been demonstrated that both NGF and BDNF not only promote expression of neuregulin-1 in NGF-dependent DRG neurons in vitro but also induce its rapid cleavage and release as an essential component of its activation (Esper and Loeb, 2004). As Schwann cells express and secrete neurotrophins (Friedman et al, 1996), these cells could, therefore, directly influence the amount of neuregulin-1 stimulation they receive via selective targeting of neurotrophins to adjacent axons. Thus, although neuregulin-1 type III remains the ultimate arbiter of ensheathment fate, developmental changes in the expression, location, and activation of the neurotrophins and their receptors could induce Schwann cell-to-axon interactions critical for coordinated peripheral nerve myelination.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that a portion of the unique sensory profile is contributed by nonmyelinating Schwann cells. These cells do respond to denervation by upregulating growth factors (Friedman et al, 1996), but the extent of this upregulation has not been determined with quantitative PCR techniques. It is also likely that the division into sensory and motor phenotypes understates the true diversity of Schwann cell expression profiles, as suggested by the diverse neurotrophin sensitivities of their parent neurons.…”
Section: Schwann Cell Phenotypementioning
confidence: 99%